(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Peer pressure may have a considerable influence on criminology students’ self-image. This research investigates how the effect of peers within the criminology academic setting changes people’s self-perception. The study looks at the effects of peer pressure on the development of self-image, identity, and decision-making in criminology students. The study intends to contribute to a better understanding of the social elements that impact the self-image of future criminologists by investigating the dynamics of peer relationships within this specific academic subject. The research methodology involves the collection of data from a randomly selected sample of 10% of the population of criminology students. Participants will be asked to complete a structured questionnaire designed to assess their experiences with peer pressure and its effects on self-image. The survey instrument incorporates Likert-scale questions and open-ended items to gather both quantitative and qualitative data. The research provides a comprehensive understanding of the multifaceted nature of peer pressure among first-year Criminology students, highlighting its influence on psychological well-being, body image, social dynamics, emotional well-being, and physical behaviors. The contextualization of the findings with existing research adds depth to the interpretation, emphasizing the need for a nuanced understanding of the interplay of social factors in shaping various aspects of students’ lives. The study investigates the effects of peer pressure on self-image among randomly selected first-year Criminology students at Bestlink College of the Philippines. The research, covering a balanced mix of male and female respondents (10% of the population), utilizes Likert scale questionnaires. Key findings indicate a dual nature of peer pressure, with both positive and negative consequences. Body image concerns, challenges in interpersonal dynamics, and a range of behaviors and attitudes among students are identified. The findings of this research may serve as a guide for educators, counselors, and policymakers to develop targeted interventions that address the specific needs and challenges faced by criminology students in managing peer pressure and enhancing their self-image. Understanding these dynamics can potentially contribute to the creation of a supportive academic environment that fosters positive self-perception and overall well-being among criminology students.